Red Ginger Reduced Pain Due to Primary Dysminorrhoea in Adolescent Girls - Hidayati, Ulfa Nur; Susanti, Nanik; Winarsih, Lilik; Wardani, Arti; Fithri, An Nisa (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Primary dysmenorrhea is common among adolescent girls and affects their quality of life and daily activities. Therefore,effective and safe treatments are needed. This study aims to evaluate the effectiveness of red ginger consumption in reducing the intensity of primary dysmenorrhea pain in adolescent girls. The research design used was a pre-experimental design with a one-group pretest-posttest design. The study was conducted at SMK